An Analysis of Strategies for Enhancing Market Share in the West Java Tissue Industry: A Case Study of PT XYZ: An Analysis of Strategies for Enhancing Market Share in the West Java Tissue Industry: A Case Study of PT XYZ - Josse, Josse carnoven; Santi Novani (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
PT XYZ, the market leader in West Java's dry tissue industry, faces market share growth stagnation due to intensifying competition and consumer price sensitivity. This study aims to analyze the internal and external factors causing this stagnation and to formulate effective business strategies to enhance PT XYZ's market share and penetration. This research employed a qualitative approach with a case study design focusing on PT XYZ. Data were collected through semi-structured interviews with key management personnel, supported by secondary data. Data were analyzed using VRIO, Porter’s Five Forces, STP, Perceptual Mapping, and Competitor Analysis frameworks, then synthesized through SWOT analysis and the TOWS Matrix. The findings identified the company's main internal strengths (such as production facilities and product quality), weaknesses (value growth stagnation and potential cannibalization), external opportunities (eco-friendly products and distribution gaps), and threats (price sensitivity and competitive pressure). Based on this analysis, key strategies were formulated, including developing innovative eco-friendly products, expanding and optimizing the distribution network, and repositioning brands for specific market segments. The implementation of these strategies is expected to sustainably enhance PT XYZ's competitiveness and market share.